WAYS TO IMPROVE ECONOMIC RELATIONS IN SMALL BUSINESS ENTERPRISES - Egamberdiev Shavkatbek Shakhobiddin ugli; Kamilova Anora Nasirovna (Лучшие интеллектуальные исследования, 2024)
Annotation. The article provides an overview of ways to improve economic relations in small business enterprises. Various proposals have been made to improve and promote economic relations. On the example of a small business enterprise, the data on it was analyzed when taking a farm.